2009
DOI: 10.1097/aog.0b013e3181c225c0
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Acetaminophen and Asthma in Children

Abstract: OBJECTIVE To estimate whether prenatal exposure to acetaminophen is associated with risk of diagnosed asthma and asthma symptoms in children. METHODS The authors prospectively followed 1,505 pregnant women and their children until 6 years (±3 months) of life. Acetaminophen use in the first and third trimesters of pregnancy was assessed before 24 weeks of gestation and within 1 month of delivery, and asthma in children was assessed when the child was 6 years old. Adjusted odds ratios (aORs) were derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 28 publications
0
45
2
2
Order By: Relevance
“…As will be evident from the descriptions of the included studies in both these meta-analyses, there was considerable heterogeneity in the methods of ascertainment of acetaminophen use and in the definitions and timing of outcome measures. Despite this, there appears to be a degree of consistency in the findings with all but one study 55 reporting increased odds or relative risk for asthma outcomes in association with acetaminophen use by mothers during pregnancy. Because of differences in study design, not all studies were able to categorise the dose used by pregnant women and those that did used different metrics.…”
Section: Acetaminophen In Pregnancy and Asthma In The Offspringcontrasting
confidence: 51%
“…As will be evident from the descriptions of the included studies in both these meta-analyses, there was considerable heterogeneity in the methods of ascertainment of acetaminophen use and in the definitions and timing of outcome measures. Despite this, there appears to be a degree of consistency in the findings with all but one study 55 reporting increased odds or relative risk for asthma outcomes in association with acetaminophen use by mothers during pregnancy. Because of differences in study design, not all studies were able to categorise the dose used by pregnant women and those that did used different metrics.…”
Section: Acetaminophen In Pregnancy and Asthma In The Offspringcontrasting
confidence: 51%
“…A weak association between paracetamol exposure during the third trimester of pregnancy and childhood asthma was shown by two studies (pooled OR=1.17, 95% CI 1.04 to 1.31, figure 2), while the three other studies that examined paracetamol exposure during the second and third trimester showed a stronger association (pooled OR=1.49, 95% CI 1.37 to 1.63, figure 2). There was significant heterogeneity among the three studies that assessed associations with paracetamol use through the entire pregnancy (Andersen et al ,13 OR=1.65, 95% CI 1.17 to 2.32; Rebordosa et al ,43 OR=1.22, 95% CI 1.11 to 1.34; Kang et al ,42 OR=0.74, 95% CI 0.5 to 1.09; I 2 =89%), so results were not pooled (figure 3). …”
Section: Resultsmentioning
confidence: 99%
“…Reasons for high levels of heterogeneity include wide range of cohort sizes, with some large cohorts providing some very tight range of effect size, some studies not allowing for confounding effect, also differences in the defined study population such as parents having allergic disease to be included into the study versus a random sample of population. Twelve of the cohort studies were selected on the basis of parents with allergic disease and of these 2 of them had ORs and 95% CIs that were outside the pooled estimate 35,36 ; however, 1 was an overestimate of the effect size and 1 was an underestimate, therefore no systematic bias was revealed within these study populations. In addition, each of these 2 studies also only contributed 3% of the overall weight to the meta-analyses and therefore overall conclusions remain the same when the studies were excluded from the meta-analyses.…”
Section: Figurementioning
confidence: 99%